(untitled) (Revista Lusófona de Educação, 2025)
Inclusive education is now recognized as a key pathway to ensuring the right of all children and young people to quality education, playing a central role in achieving the goals of the 2030 Agenda for Sustainable Development. This thematic issue brings together a set of studies that examine and share understandings and practices regarding student diversity — including ethnic, cultural, linguistic, and socio-economic diversity — in the face of complex challenges such as unequal access to resources and opportunities, negative attitudes toward inclusion, teacher training, demographic changes, increasing migration flows, climate change, and more.